The Canary Caper - Roy, Ron 1940-; Gurney, John (New York : Random House, 1998)
Dink and his friends investigate why pets, like Mrs. Davis's canary, Mozart, are mysteriously disappearing all over town.
"A Stepping Stone book."
"Grades 2-4"--cover p. [].
Keywords: Pets -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories